Hoarseness of Voice : An Etiological Study (Bangladesh Journal of Otorhinolaryngology, 2020)
Hoarseness of voice is one of the commonest symptom in otolaryngological practice and it indicates diseases ranging from totally benign condition to the most malignant condition. The aim of this study was to analyze clinical profile, to find out common etiological factors and association of common predisposing factors leading to hoarseness of voice. The study was carried out in the department of ENT, CMB, BAF Dhaka, from February 2014 to July 2016. A total of 130 patients having hoarseness of voice were selected coming to the OPD. All the patients then underwent a detailed history, ENT examinations and investigations to reach a diagnosis. Out of total 130 patients 76(58.47 %) were males and 54 (41.53) were females. Male predominance was observed with male female ratio of 1.49: 1. Common age group involved was 31- 40 years in 29 (20.7%) cases. Common etiology included chronic laryngitis in 37 (28.46%) cases, vocal nodules in 20 (15.38%), vocal cord polyp in 18 (13.84%), acute laryngitis in 10 (7.69%), vocal cord cyst in 9 (6.92%), hypothyroidism in 7 (5.38%) and Carcinoma larynx in 6 (4.61%) patients. Most of the etiopathological factors found in this study were treatable disease. So, early diagnosis can reduce the morbidity and mortalityBangladesh J Otorhinolaryngol; April 2017; 23(1): 47-51